Rayville, Norton County - Hutchinson, Hannah (Kansas State University, The Chapman Center for Rural Studies, 2017)
This study examines the town of Rayville in Almena Township, Norton County, Kansas. It lasted from 1885 to 1902. By networking with surrounding communities and research at Norton Historic Society I could find more about this small community than I thought existed. My study includes maps, atlases, newspaper articles, personal photographs, and field work.
Hannah Hutchinson, “Rayville, Norton County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/197.
Keywords: Norton County; Rayville; Dutch-Americans; George W. Rhanny; The Netherlands; Almena Township